Numerical Simulation of Seismoacoustic Wave Transformation at Sea–Land Interface - Grigory Dolgikh; Mikhail Bolsunovskii; Denis Zharkov; Ruslan Zhostkov; Dmitriy Presnov; Andrey Razin; Andrey Shurup (Journal of Marine Science and Engineering)
This study considers seismoacoustic wave propagation through the land–sea interface, i.e., in the presence of a coastal wedge, taking into account the real bottom bathymetry. It is of interest in the problems of coastal monitoring and environmental studies. An effective numerical model based on the finite element method is proposed and implemented. An approximate analytical solution in the fluid and an asymptotic analytical solution for the surface seismic wave on the shore are considered to validate the numerical model. It is shown that in field experiment conditions the hydroacoustic signal generated by an underwater source with a power of ~200 W is transformed into a seismic wave on the shore with an amplitude of units of nanometers at distances of several kilometers, which can be measured by a sensitive sensor. An extensive series of numerical simulations with different model parameters was performed, which allowed us to evaluate the most appropriate propagation medium parameters to match the observed and calculated data.